Wealth : NOMOS LVIII. - Knight, Jack (NOMOS - American Society for Political and Legal Philosophy., 2017)
An in-depth political, legal, and philosophical study into the implications of wealth inequality in modern societies.Wealth, and specifically its distribution, has been a topic of great debate in recent years. Calls for justice against corporations implicated in the 2008 financial crash; populist rallying against "the one percent"; distrust of the influence of wealthy donors on elections and policy--all of these issues have their roots in a larger discussion of how wealth operates in American economic and political life. In Wealth a distinguished interdisciplinary group of scholars in political science, law and philosophy address the complex set of questions that relate to economic wealth and its implications for social and political life in modern societies. The volume thus brings together a range of perspectives on wealth, inequality, capitalism, oligarchy, and democracy. The essays also cover a number of more specific topics including limitarianism, US Constitutional history, the wealth defense industry, slavery, and tax policy. Wealth offers analysis and prescription including original assessment of existing forms of economic wealth and creative policy responses for the negative implications of wealth inequality. Economic wealth and its distribution is a pressing issue and this latest installment in the NOMOS series offers new and thought provoking insights.